2020
DOI: 10.1016/j.jinf.2020.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections in people with COVID-19: a systematic review and meta-analysis

Abstract: Objectives: In previous influenza pandemics, bacterial co-infections have been a major cause of mortality. We aimed to evaluate the burden of co-infections in patients with COVID-19. Methods: We systematically searched Embase, Medline, Cochrane Library, LILACS and CINAHL for eligible studies published from 1 January 2020 to 17 April 2020. We included patients of all ages, in all settings. The main outcome was the proportion of patients with a bacterial, fungal or viral co-infection. . Results: Thirty studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

92
1,279
30
72

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,353 publications
(1,621 citation statements)
references
References 64 publications
92
1,279
30
72
Order By: Relevance
“…Co-infections in COVID-19 have been described in previous studies (often within larger studies including all hospitalized COVID-19 patients), and reported incidence varies greatly, according to de nition criteria, the heterogeneity of patients included and the diagnostic methods used. We observed a higher incidence of nosocomial infections compared to those reported in some recent meta-analysis [5,6,12]. However, when we compared our results with those of studies that only included COVID-19 patients hospitalized in the ICU, we observed more similar results [11,[13][14][15][16].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Co-infections in COVID-19 have been described in previous studies (often within larger studies including all hospitalized COVID-19 patients), and reported incidence varies greatly, according to de nition criteria, the heterogeneity of patients included and the diagnostic methods used. We observed a higher incidence of nosocomial infections compared to those reported in some recent meta-analysis [5,6,12]. However, when we compared our results with those of studies that only included COVID-19 patients hospitalized in the ICU, we observed more similar results [11,[13][14][15][16].…”
Section: Discussionsupporting
confidence: 74%
“…Some small studies have described the occurrence of infection sustained by MDR gram negative bacteria (Enterobacterales, A. baumannii, P. aeruginosa) [5,12], others have found the commonest bacteria to be Mycoplasma pneumoniae, P. aeruginosa, H. in uenzae and Klebsiella spp. [6]. A recent single centre study from Barcelona reported a similar microbiological pattern to the one we observed, however this study included all hospitalized patients and did not differentiate between infections acquired in the ICU and in hospital wards [25].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…HDL and Apo-AI may help in preventing in ammatory injury and improving the clinical outcome with anti-in ammatory and antioxidative properties. Then, a systematic review and meta-analysis showed that bacterial co-infection occurred in 7% of hospitalized COVID-19 patients and 14% of ICU patients, and the bacterial co-infection would lead to a higher mortality of COVID-19 [37]. Studies showed that HDL was capable to bind and neutralize Gram-negative LPS and Gram-positive lipoteichoic acid (LTA), thus reducing LTA and LPSinduced in ammatory injury [38,39], thus providing the conception that HDL-based therapies might be promising in severe COVID-19 patients with bacterial co-infection.…”
Section: Discussionmentioning
confidence: 99%
“…But even among a wide number of articles reporting on COVID-19 clinical data, only a few have reported secondary infection, mostly without detailed pathogens. Some reported a low proportion of superinfections in hospitalized patients (7-8%) that rose to 14% in ICU, less than in previous in uenza pandemics [46]. According to other data, secondary infections were identi ed in 5%-44% of ICU patients with COVID-19, being bacterial or fungal pneumonia and bloodstream the most frequent infections [47] (23a), as in our cohort (VAP 38.6% and BSI 36.8%), where the total number of superinfections is higher overall.…”
Section: Discussionmentioning
confidence: 90%